Are Women Breaking the Poverty Trap? Changes in Poverty, Income, and Women's Empowerment in Southwestern Bangladesh - Ahmed, Akhter (2018)
Using two survey rounds from IFPRI's Bangladesh Integrated Household Survey (BIHS), IFPRI researchers from the Bangladesh Policy Research and Strategy Support Program (PRSSP) analyze trends on poverty and women's empowerment in southwest Bangladesh between 2011/12 and 2015.